A world beneath the sands : the golden age of Egyptology - Wilkinson, Toby., 1969- (W. W. Norton & Company, 2020)
"A thrilling history of the West's scramble for the riches of ancient Egypt by the foremost Egyptologist of our time. From the decipherment of hieroglyphics in 1822 to the discovery of Tutankhamun's tomb by Howard Carter and Lord Carnarvon a hundred years later, the uncovering of Egypt's ancient past took place in an atmosphere of grand adventure and international rivalry. In A World Beneath the Sands, the acclaimed Egyptologist Toby Wilkinson chronicles the ruthless race between the British, French, Germans and Americans to lay claim to its mysteries and treasures. He tells the riveting stories of the men and women whose obsession with Egypt's ancient civilization helped to enrich and transform our understanding of the Nile Valley and its people, and left a lasting impression on Egypt, too. Travelers and treasure-hunters, ethnographers and archaeologists: whatever their motives, whatever their methods, a century of adventure and scholarship revealed a lost world, buried for centuries beneath the sands"--